Effect of Citrus sinensis and Musa textilia Consumption on Lactic Acid Levels and Muscle Tension in Fish Auction Workers - Kurniawan, Bina; Rahfiludin, Mohammad Zen; Setyaningsih, Yuliani; Nurjazuli, Nurjazuli (Media Kesehatan Masyarakat Indonesia, 2024)
Potassium deficiency is known to induce muscle fatigue, necessitating the inclusion of potassium-rich foods, such as orange (Citrus sinensis) and banana (Musa textilia) in diet. Previous studies have shown that consuming 150 g and 300 g of banana is effective in preventing muscle fatigue, with orange containing 237.4 mg of potassium per 300 ml. Therefore, this study aims to examine the relationship between lactic acid concentration and muscle tension reduction in fish auction workers after the administration of orange and banana. The study procedures were carried out with a quasi-experimental pre-test and post-test group design, and the samples were divided into 4 groups. Group 1 received both orange and banana, 2 was given only orange, 3 received only banana, while 4 was not given any intervention. Supplemental observations were then conducted over 3 consecutive days, followed by data analysis using Two-Way Analysis of Variance (ANOVA) and Multivariate Analysis of Variance (MANOVA) to compare lactic acid levels (independent variable) with muscle tension and strength (dependent variables). The results showed that banana significantly affected lactic acid levels but did not influence muscle tension. The combination of orange and banana produced varying levels of lactic acid and muscle tension, indicating the ineffectiveness of only banana. The intake of both fruits was also reported to influence lactic acid levels but did not affect muscle strength, suggesting the ineffectiveness of orange. These results indicated that while orange and banana could reduce lactic acid levels, the fruits did not significantly affect muscle strength or tension.